Bridging between Research and Practice Supporting Professional Development through Collaborative Studies of Classroom Teaching with Technology - Hennessy, Sara (Professional Learning, 2014)
This book presents a fresh approach to bridging the perceived gap between academic and classroom cultures. It describes a unique form of research partnership whereby Cambridge University academics and school teachers together grappled with and reformulated theory-through in-depth case studies analysing practice using interactive whiteboards in five subject areas. The inquiry exploited the collaborators' complementary professional knowledge bases. Teachers' voices are particularly audible in co-authored case study chapters. Outcomes included deeper insights into concepts of sociocultural learning theory and classroom dialogue, more analytical mindsets, sustained new practices and ways of working collegially.; Readership: The book will interest academic and teacher researchers, initial teacher educators, professional development leaders, mentors, plus practitioners interested in using interactive whiteboards and dialogic teaching. It explores widening approaches to collegial development to reach educators working in other contexts (with and without technology). This could involve intermediate theory building or shortcutting by sharing and adapting the outcomes-springboarding teachers' further critique and professional learning.